Cesto orgânico: um projeto piloto na web que aproxima produtores e consumidores de orgânicos - Verde, Eula Lôbo Netto Vila (2018)
The approach organic producers and consumers is the inspirational ideal of the Cesto Orgânico platform. Developed on the web, the product seeks to democratize the access routes to organic production, in a way to recognize the origin of its food and to value the role of rural producers in our country. The purpose also is engaging communication with social and environmental causes, which discuss the dichotomy between consumption and ecology. The position is that the organic is a way for a more responsible agriculture in relation to the environment and our health, in addition to establishing more just relations. There are the visual identity and the portal of the Cesto Orgânico. The site can be accessed through the address cestoorganico.com.br. However, the platform remains evolving according to the participation of organic producers and consumers. This work involves a theoretical framework with the rescues of the history of agriculture in Brazil, the rise of the organic production movement in the world, the Brazilian legislation and also demonstrates the results of a research in the region of Goiânia with producers of organic foods at fairs. The records of this data contemplate the enthusiasm of the rural producers with new modalities of commercialization and with the participation in projects of communication online. Result of a scientific research, with the endorsement of the Graduate Program in Technologies, Communication and Education of the Federal University of Uberlândia, the project reinforces the commitment and the social responsibility of the Brazilian universities.